Communication strategy of public relation in building competiveness of higher education quality: A case of stain Tengku Dirundeng Meulaboh - Mukhsinuddin Mukhsinuddin (Proceedings of AICS - Social Sciences, 2017)
The basic purpose of understanding the Strategy is planning and management to accomplish a goal, "Public Relation". The base author’s purpose of doing this research knowing on how communication strategic Public Relation of STAIN Teungku Dirundeng Meulaboh in building competitiveness and excellence image quality of education in Aceh. Based on the objectives with regard to the approach used in this research was the qualitative approach. The method performed using by observation, in-depth interviews, and documentation. While as a counterbalance, Public Relation must preserve manage internal media, either in the form of magazines, printed publications (leaflets, brochure, poster, outdoor graphic) to the special reports to be shown on internal and external campus media. Technology and information media used is print and electronic media. Indonesia printing media is the Serambi Indonesia, Rakyat Aceh and Analisa. In addition, through online media as Aceh Trend, Aceh Pos, AJNN, Media and official Website of Teungku Dirundeng STAIN Meulaboh, Aceh.